Special Protection for Children as Victims of the Crime of Sending Children - Audyna Mayasari Muin; Arnita Pratiwi Arifin (Faculty of Law, Universitas Pekalongan, 2023)
Protection of children from a crime is not only regulated in Law Number 23 of 2002 concerning Child Protection in conjunction with Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. It is also regulated in Law Number 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons. The philosophy of regulating the crime of trafficking in persons is to protect women and children from exploitation by subjects of criminal law. The crime of sending children is regulated in Article 6 of the PTPPO Law. The formulation of criminal acts in Article 6 is a representation of both preventive and repressive legal protection against children as victims of criminal acts. In contrast, the inclusion of criminal sanctions in prison and fines and confinement in lieu of fines in Article 6 of the PTPPO Law is a development of the theory of the purpose of punishment, namely the theory of balance that accommodates not only the interests of the victims but also of the perpetrators and society. The form of protection given to children as victims of shipping crimes which is regulated in the PTPPO Law is restitution and rehabilitation. As a result, the author concludes that along with restitution and rehabilitation, children are also provided with medical assistance, psychosocial rehabilitation, and psychological rehabilitation as regulated in the LPSK Law